A five-year retrospective review of snakebite patients admitted to a tertiary university hospital in Malaysia. - Chew, Keng Sheng; Khor, Heng Wei; Ahmad, Rashidi; Rahman, Nik Hisamuddin Nik Abdul (2011)
BACKGROUND